Lived Experience of People Living with HIV/AIDS Undergoing Antiretroviral Therapy: A Qualitative Study - RTS Netisa Martawinarti; Nursalam Nursalam; Andri Setiya Wahyudi (Jurnal Ners, 2020)
Introduction: Antiretroviral therapy is an important factor in improving the quality of life of HIV sufferers, but a complex problem in HIV sufferers is a trigger factor for non-compliance in undergoing ARV therapy. The purpose of this study was to explore the experience of people living with HIV/AIDS (PLWHA) undergoing antiretroviral treatment.Methods: This study was a qualitative phenomenological study, with a sample of 13 HIV patients (10 men and 3 women) who were taking antiretroviral therapy for more than one year; they were recruited using purposive sampling techniques, and data were collected through in-depth semi-structured interviews, field notes and document reviews. Data were analyzed using the Colaizzi method which consists of nine stages.Results: There were six themes that emerged from the experience of PLWHA undergoing antiretroviral therapy and these became the subject of this study, namely knowledge of HIV disease and antiretroviral drugs, self-motivation, social support, and skills in undergoing treatment (self-management), adherence, and quality of life.Conclusion: Of the six themes that emerged, poor knowledge (understanding of the disease and its treatment), social support and self-management were the main factors that were obstacles to and causes of treatment failure; this was due to the unpreparedness for receiving information at the beginning of treatment, lack of motivation, and ignorance in behavior when people had problems with medication.